Exploring Hybrid Vehicle Integration in Nablus Urban Shared-Taxis: Cost-Benefit and Exhaust Emissions Assessment - Sharif Bassam Salman; Khaled Al-Sahili (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
There is a worldwide concern about the increase in vehicles’ exhaust emissions of traditional fuels and the rise in fuel prices. Nablus city is a major city in the West Bank, Palestine with peculiar topography and traffic congestion. This increases fuel consumption and the gas emission of the diesel operated public transport (PT) shared-taxi vehicles. This paper investigates the viability of introducing hybrid vehicles to the urban shared-taxis in highly congested areas with peculiar topography. Interviews were conducted and questionnaires were distributed among PT drivers and route managers to obtain the operational and cost characteristics of each route. The existing expenses and revenues and gas emissions of diesel vehicles were analyzed. Expenses-revenues analysis revealed that there is no immediate urgency in switching all diesel-fuel shared-taxis to hybrid; therefore, two scenarios were developed. The first was replacing old PT cars (2009 or older) with hybrid vehicles, which provided an average financial saving of 20.9% with a reduction in exhausts emission of CO2-equivalent by 33%. The second scenario included replacing PT vehicles with production dates from 2009-2014, which produced financial savings of 15% and reduction of exhaust emissions by 35%. The comparison showed a preference for the first scenario at the current time, while implementing other scenarios gradually. The first scenario is simple and close to reality; as old vehicles should typically be replaced. The study recommends using hybrid vehicles for new shared-taxis introduced to the service, and establishing national level policies to encourage the use of alternative fuels for the transportation sector, focusing on PT. However, several critical factors must be considered, including topography and route characteristics.